Splenic artery embolization for trauma: a narrative review - Simon Roh (Journal of Trauma and Injury)
The management of traumatic splenic injuries has evolved significantly over the past several decades, with the majority of these injuries now being treated nonoperatively. Patients who exhibit hemodynamic instability upon initial evaluation typically require surgical intervention, while the remainder are managed conservatively. Conservative treatment for traumatic splenic injuries encompasses both medical management and splenic artery angiography, followed by embolization in cases where patients exhibit clinical signs of ongoing splenic hemorrhage. Splenic artery embolization is generally divided into two categories: proximal and distal embolization. The choice of embolization technique is determined by the severity and location of the splenic injury. Patients who retain functioning splenic tissue after trauma do not routinely need immunization. This is in contrast to post-splenectomy patients, who are at increased risk for opportunistic infections.